The gene regulatory cascade linking proneural specification with differentiation in Drosophila sensory neurons. - Sebastián Cachero; T Ian Simpson; Petra I Zur Lage; Lina Ma; Fay G Newton; Eimear E Holohan; J Douglas Armstrong; Andrew P Jarman (PLoS Biology)
In neurogenesis, neural cell fate specification is generally triggered by proneural transcription factors. Whilst the role of proneural factors in fate specification is well studied, the link between neural specification and the cellular pathways that ultimately must be activated to construct specialised neurons is usually obscure. High-resolution temporal profiling of gene expression reveals the events downstream of atonal proneural gene function during the development of Drosophila chordotonal (mechanosensory) neurons. Among other findings, this reveals the onset of expression of genes required for construction of the ciliary dendrite, a key specialisation of mechanosensory neurons. We determine that atonal activates this cellular differentiation pathway in several ways. Firstly, atonal directly regulates Rfx, a well-known highly conserved ciliogenesis transcriptional regulator. Unexpectedly, differences in Rfx regulation by proneural factors may underlie variations in ciliary dendrite specialisation in different sensory neuronal lineages. In contrast, fd3F encodes a novel forkhead family transcription factor that is exclusively expressed in differentiating chordotonal neurons. fd3F regulates genes required for specialized aspects of chordotonal dendrite physiology. In addition to these intermediate transcriptional regulators, we show that atonal directly regulates a novel gene, dilatory, that is directly associated with ciliogenesis during neuronal differentiation. Our analysis demonstrates how early cell fate specification factors can regulate structural and physiological differentiation of neuronal cell types. It also suggests a model for how subtype differentiation in different neuronal lineages may be regulated by different proneural factors. In addition, it provides a paradigm for how transcriptional regulation may modulate the ciliogenesis pathway to give rise to structurally and functionally specialised ciliary dendrites.